A Chemically Defined Serum-Free Culture System for Spontaneous Human Mesenchymal Stem Cell Spheroid Formation. (7th March 2020) - Zhao, Yajun; Xiao, E.; Lv, Wanqi; Dong, Xian; He, Linhai; Wang, Yixiang; Zhang, Yi
Abstract : Mesenchymal stem cells (MSCs) possess promising potential in tissue engineering and regenerative medicine. Previous studies demonstrated that spheroid formation of MSCs exhibited improved stemness maintenance and therapeutic potential compared with monolayer culture. To date, various spheroid culture systems have been developed but most of them required low adhesion conditions or special equipment. In this study, we demonstrated that inoculation of dissociated MSCs in TeSR-E8 medium could induce self-assemble spheroid formation in conventional tissue culture polystyrene dishes. Compared with monolayer culture, adipose-derived stem cell (ADSC) spheroids enhanced the proliferation and osteogenic capability of ADSCs compared with monolayer culture. When reseeded in normal serum-containing medium, the expression level of stemness biomarkers was even higher in spheroid-derived ADSCs than monolayer culture. Importantly, spheroid ADSCs could effectively promote the M2 polarization of macrophages both in vitro and in vivo . After transplantation into mouse, spheroid ADSCs improved the survival rate and significantly decreased serum levels of proinflammatory factors IL-1 β and TNF- α following LPS challenge. In summary, we developed a 3D spheroid culture system through TeSR-E8 medium without the involvement of low adhesion conditions and special equipment, which provided a practical and convenient method for spheroid formation of MSCs with great potential for stem cell clinical therapy.